Market Integration: An Application of Co-integration and Error Correction Model to Rice Markets in Bangladesh (The Agriculturists, 2010)
The study was conducted to investigate the degree and nature of spatial integration among district level monthly wholesale price of rice in Northwestern and greater Mymensingh region of Bangladesh. Market integration was examined by co-integration method-while price fluctuations were estimated by Error Correction Mechanism (ECM). Stationarity of data was checked with the help of Augmented Dickey-Fuller (ADF) ('tau') test. Unit root test indicated that all the price series were non-stationary at level (original form of data), but were stationary after first difference. Engle Granger integration test indicated that all of the pair wise coefficients of price series were greater than the critical value at 1% level of significance implying strong and close proximity of inter regional price linkage, attributed to good communication, better infrastructural facilities etc. Therefore, wholesale price of paddy/rice at the regional level were spatially integrated in the long run even though rice markets were geographically dispersed. The extent of degree of integration demonstrated strong association (as all the coefficients were significant at 1% level), which is an indicator of efficient, and competitive marketing system, ultimately ensured maximum returns to the producers as well as expected reasonable price of the consumers. Though Law of One Price (LOP) was not effective between any market pairs, yet price signals reached the relevant sources appropriately. The distance between markets as a causal factor did not appear to be an impediment to efficient/inefficient adjustment of price to new information.